The Effectiveness of Timeline Story Poster on Learning Outcames in Islamic Historical Lesson - Luthfana, Hana Aisyatul; Muhtadi, Ali; Azizah, Nurul; Nurahmah, Riska Hanan; Salim, Khairunnisa Binti Mohd (Universitas Islam Negeri Raden Intan Lampung, 2024)
Islamic historical lessons are often considered boring and uninteresting. This is known by the existence of a significant point of difference between the average score obtained and the minimum average level of achievement. The average score in the Islamic History subject for Class 3 Intensive 2021 students is 2.62, while the minimum score is 4.9. From this data, it was found that only 1% of students reached the minimum limit. Therefore, this research was carried out with the research method used was quantitative experimental type. The population was all Intensive Class 3 students and the sample selection technique was simple random sampling, which took 70 students from Intensive Class 3 B to Intensive Class 3 H, half of whom were students for the control class and 35 students for the experimental class. The analysis uses the normality test, reliability test, and Mann Whitney test. This study shares new findings, namely forms of application and obstacles in understanding Islamic history lessons. In this research it can also be seen that students' understanding and learning outcomes are very minimal. This research recommends the use of Timeline Story Poster-based learning media to improve learning of Islamic history education. Teachers need to develop innovative learning media strategies, while students must actively participate in the learning process and apply their experiences. With the timeline story poster, students can realize their desire to study Islamic history easily and happily. Meanwhile, teachers can use the results of this research as a reference in applying educational methods in the learning process.